Airborne Microplastics: Challenges, Prospects, and Experimental Approaches - Alexey R. Rednikin; Yulia A. Frank; Artem O. Rozhin; Danil S. Vorobiev; Rawil F. Fakhrullin (Atmosphere)
Airborne microplastics are emerging pollutants originating from disposable tableware, packaging materials, textiles, and other consumer goods. Microplastics vary in shape and size and exposed to external factors break down into even smaller fractions. Airborne microplastics are abundant in both urban and natural environments, including water bodies and glaciers, as particles can travel long distances. The potential toxicity of airborne microplastics cannot be underestimated. Microparticles, especially those < 10 µm, entering the human body through inhalation or ingestion have been shown to cause serious adverse health effects, such as chronic inflammation, oxidation stress, physical damage to tissues, etc. Microplastics adsorb toxic chemicals and biopolymers, forming a polymer corona on their surface, affecting their overall toxicity. In addition, microplastics can also affect carbon dynamics in ecosystems and have a serious impact on biochemical cycles. The approaches to improve sampling techniques and develop standardized methods to assess airborne microplastics are still far from being perfect. The mechanisms of microplastic intracellular and tissue transport are still not clear, and the impact of airborne microplastics on human health is not understood well. Reduced consumption followed by collection, reuse, and recycling of microplastics can contribute to solving the microplastic problem. Combinations of different filtration techniques and membrane bioreactors can be used to optimize the removal of microplastic contaminants from wastewater. In this review we critically summarize the existing body of literature on airborne microplastics, including their distribution, identification, and safety assessment.